IoT Based Vehicle Safety Controller Using Arduino - Said Achmad; Raditya Adinugroho; Nur Safii Hendrawan; Thomas Franklin (Bina Nusantara University, 2023)
Several people try to break into vehicles and steal vehicles left by their owners, sometimes even without the owner's knowledge. There are still various ways that can be done to a turn on the vehicle without the key from the vehicle so that the vehicle can be stolen easily. Due to the ease of break-in from some vehicles, several additional security implementations can be installed. One of these ways is to implement IoT and RFID. There are several implementations of IoT as an extra device for safety and tracking vehicles. RFID can be Implemented as an additional key or access. IoT and RFID can be combined to provide additional safety for vehicles and prevent vehicle theft. This research aims to propose a device that uses IoT technology and RFID to keep the vehicle safe and track the use of the vehicle. This research use Arduino, RFID, and GPS module. The proposed device was tested under various conditions of RFID use and the level of accuracy of the GPS module used. The test results show that the proposed tool can work well for security and tracking needs.